Simulated past and future ice geometry of Cook Glacier, East Antarctica - Jordan, James; Stokes, Chris; Gudmundsson, G. Hilmar; Jenkins, Adrian; Miles, Bertie; Jamieson, Stewart (NERC EDS UK Polar Data Centre, 2021)
Input and results files for the ice dynamics model Ua simulating potential past and future ice geometry of Cook Glacier, East Antarctica. Results seek to explain potential causes of recent observed acceleration and speculate on future causes of acceleration. This work was funded by NERC grant NE/R000719/1. : Data was generated using the Ua (version 2019b) ice dynamics model. : Ua ice dynamics model, version 2019b. : Simulations are for 1973, 1989 and 2017 configurations of Cook Ice shelf, as well as potential future configurations with no specified date. Model mesh varies from 250m resolution at the grounding line to 5km further inland.